When the Distressed Teach the Oppressed: Toward an Understanding of Communion and Commitment - Christopher Ferry (Journal of the Assembly for Expanded Perspectives on Learning, 1996)
Jane Tompkins' adaptation of Paulo Freire's educational philosophy is critiqued through exploring the spiritual basis of his idea of the "Easter experience."